2023
DOI: 10.1039/d3mh01054f
|View full text |Cite
|
Sign up to set email alerts
|

Infected wound repair with an ultrasound-enhanced nanozyme hydrogel scaffold

Fan Zhang,
Yong Kang,
Liwen Feng
et al.

Abstract: Chronic diabetic wounds persistently face the threat of evolving into diabetic foot ulcers owing to severe hypoxia, high levels of reactive oxygen species (ROS), and a complex inflammatory microenvironment. To...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…169 Zhang et al designed a nanoenzyme-hydrogel scaffold (PNAs). 170 Under ultrasound, the surface plasmon resonance effect enhanced electron polarisation, effectively catalysing hydrogen peroxide, promoting glutathione synthesis, and enhancing the ROS scavenging ability. PNAs promote in vitro cell proliferation, migration, and angiogenesis, promote diabetic wound healing in vivo, and control the release of antibacterial components according to changes in specific active substances in infected wounds.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…169 Zhang et al designed a nanoenzyme-hydrogel scaffold (PNAs). 170 Under ultrasound, the surface plasmon resonance effect enhanced electron polarisation, effectively catalysing hydrogen peroxide, promoting glutathione synthesis, and enhancing the ROS scavenging ability. PNAs promote in vitro cell proliferation, migration, and angiogenesis, promote diabetic wound healing in vivo, and control the release of antibacterial components according to changes in specific active substances in infected wounds.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…Zhang et al designed a dynamic covalent bond hybrid of a metal–organic coordination polymer as a synthesis template (PNAs) to obtain a high-density platinum nanoparticle assembly. 89 The tight assembly of this compact platinum nanoparticle effectively mimics the antioxidant enzymes (CAT, POD). Through a series of enzymatic kinetics and in vitro studies, the authors confirmed that PNAs can simulate CAT and POD and catalyze hydrogen peroxide to produce O 2 and water (Fig.…”
Section: Gas Treatment Of Chronic Diabetic Wounds: (Treatment Of Chro...mentioning
confidence: 99%
“…An alternative strategy to combat hypoxia and boost cell survival involves incorporating catalase into the hydrogel system, although this approach is limited to ROS-accumulated areas, as oxygen generation relies on the catalase-mediated H 2 O 2 decomposition. 194 , 195 …”
Section: Hydrogels For Cell Therapymentioning
confidence: 99%